PENGARUH EMOTIONAL INTELLIGENCE, SPIRITUAL INTELLIGENCE, WORK MOTIVATION, DAN JOB SATISFACTION TERHADAP TEACHER PERFORMANCE DI SD XYZ CABANG TANGERANG - Theresiana Erna Retnawati; Ardi, Ardi (Media Bina Ilmiah, 2024)
This study analyzes the influence of emotional intelligence, work motivation, spiritual intelligence, and job satisfaction on teacher performance. This quantitative study uses PLS-SEM (Partial Least Square-Structural Equation Modeling) with data collection using a questionnaire. The study involves all 100 elementary school teachers from the XYZ branch of Tangerang and data processing using SmartPLS. The research results show that emotional intelligence, spiritual intelligence, and job satisfaction have a positive effect on teacher performance, while emotional intelligence, spiritual intelligence, and work motivation have a positive effect on job satisfaction. The results also show that the emotional intelligence variable has a positive effect on spiritual intelligence, but spiritual intelligence has a negative effect on job satisfaction